Proliferation of myeloid lineage cells and apoptosis of lymphoblastic leukemic cells induced by short-course high-dose methylprednisolone in patients with acute lymphoblastic leukemia - Yıldıran, Alişan; Erduran, Erol; Tekelioğlu, Yavuz; Dilber, Embiya; Gedik, Yusuf (The Turkish Journal of Pediatrics, 2002)
In this paper, we investigated the effects of short-course high-dose methylprednisolone (HDMP) treatment on the proliferation of myeloid lineage cells and on apoptosis of blast cells in eight children with acute lymphoblastic leukemia (ALL). The patients were given the HDMP treatment (30 mg/kg/d, perorally) before 9:00 a.m. for seven days. Bone marrow (BM) aspiration was done at days 0 and 3 of the HDMP treatment in all patients and at the 7th day of the HDMP treatment in six patients. Bone marrow blast cells had gradually decreased after the HDMP treatment by the 7th day. There were statistically significant differences between the mean percentages of BM blast cells at days 0 and 3, days 0 and 7, and at days 3 and 7 (p<0.05). The mean percentages of blast cell apoptosis at the 3rd day was significantly higher than at days 0 and 7, and apoptosis at day 0 was significantly lower than at the 7th day (p<0.05). The mean percentages of BM myeloid lineage cells at the 7th day was significantly higher than at days 0 and 3 (p<0.05), and the mean percentage at day 0 was significantly lower than at the 3rd day (p<0.05). These findings indicate that short-course HDMP treatment causes apoptosis on lymphoblasts and increases the proliferation of myeloid lineage cells in children with ALL.